Efeito metafilático do disseleneto de difenila na saúde de bezerras holandesas - Rodrigues, Cláudia Medeiros (2019)
The objective of this work was to evaluate the metaphylactic effect of diphenyl diselenide (PhSe)2 on the health of Holstein calves from birth to weaning. Twenty female Holstein calves from birth to seventy days old were used, distributed in two groups of 10 animals. The diphenyl diselenide group (DDG) received 1.5 µmol/kg of (PhSe)2 diluted in 2 mL of dimethylsulfoxide (DMSO) subcutaneously (SC), while the control group (CG) received only DMSO in the same volume, SC. The applications were performed on days 7, 21, 35 and 49 of life. Clinical evaluations, weighing and sample collection were performed on the same administration days, with a final evaluation on day 70. Higher values of weight and mean daily weight gain (MDWG) were observed at day 70 in DDG compared to CG (p < 0.05). At weaning (70 days) DDG presented an average of 7.7 kg more than CG. However, for the variables incidence of diseases, serum protein, thiobarbituric acid reactive substances (TBARS), glutathione peroxidase (GPx) and oxidative metabolism and neutrophil phagocytosis no significant differences were observed between the groups (p > 0.05). With respect to immunoglobulin G (IgG), except for day 7, higher levels were detected in the DDG compared to the CG (p < 0.05), and within the DDG the calves showed a gradual increase of IgG throughout the experimental period. The results allow us to affirm that metaphylaxis with (PhSe)2 increases the weight gain and immunity of Holstein calves from the neonatal period to weaning.